Evaluation of Modeling Procedures for a Soft-Bodied Robot. - McHugh, Steven. (2017)
Abstract: This thesis details two major contributions in the design of highly deformable robots used for Urban Search and Rescue missions. The first contribution of the thesis is a proposed method for obtaining optimized 3D model generation from abstract simulation outputs, while leveraging the benefits of both optimization techniques and human-centric design. The second contribution is a demonstration that a properly constrained simulation is highly beneficial to finding realizable models, as well as a series of tests that ensure the proposed constraints do not significantly hinder the genetic algorithm's search space. To verify the proposed methods, a prototype was designed and tested. The result of the experiment was a partial verification of these methods, in that it showed the methods are feasible to implement, but the experiment also highlighted some challenges that remain in accounting for additional complexities, especially modeling actuator attachment and the effects of contact between the actuators and the body of the robot.; Thesis (M.S.)--Tufts University, 2011.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Jason Rife.; Committee: Rob White, and Soha Hassoun.; Keywords: Robotics, Engineering, and Computer science.